Canine ehrlichiosis: prevalence and epidemiology in northeast Brazil - Guedes,Paula Elisa Brandão (2015)
Ehrlichiosis is a zoonotic disease that is caused by bacteria of the genus Ehrlichia. The aims of this study were to detect the presence of Ehrlichia spp. in the blood of dogs in Ituberá, Bahia, and to compare the sensitivities and specificities of blood smear, serological, and molecular examinations. Furthermore, this study identified factors associated with exposure to the agent in dogs in this locality. Blood samples were collected from 379 dogs and submitted for indirect immunofluorescent assay and polymerase chain reaction testing for the detection of Ehrlichia spp. antibodies and DNA, respectively. Additionally, a peripheral blood smear was obtained from the ear tip for parasite identification. Of the 379 animals, 12.4%, 32.7%, and 25.6% were identified as positive on the blood smear, serological, and molecular tests, respectively. The dogs positive in one of the three techniques were considered exposed (46.9%). Younger dogs and rural habitat were protective factors and presence of ticks and contact with other dogs were the risk factors associated with exposure to the agent. It was concluded that dogs of Ituberá have high positivity for Ehrlichia spp. and that the diagnostic methods used for detection are complementary.